EKSPRESI IBU DALAM KARYA SENI LUKIS EKSPRESIONISME - Drs. Syafwan, M.Si., IMEL MANDASARI, Drs. Ariusmedi, M.Sn., (Serupa The Journal of Art Education, 2017)
The purpose of the creation of this final work is to visualize the expression of the mother through the expression of expressionist painting. Mother figure of a remarkable woman for 9 months 10 days, struggling to risk his life for the salvation of the baby. The method of creation of artwork using five stages of preparation stage, elaboration stage, synthesis stage, stage of concept realization and completion stage and the last exhibition Painting .. Ten masterpiece was visualized The mother's struggle for her child was not fully reciprocated. Evidently there are some children who are not filial to parents, especially mothers. In running a life it is not appropriate for a child to sue, scold and say harshly to his mother. Because of these problems the mother becomes depressed, depressed, sad and sick.Kata kunci: Ekspresi Ibu, Seni Lukis Ekspresionisme